Specialty preferences among medical students in Botswana - Ambrose Rukewe; W. A. Abebe; A. A. Fatiregun; M. Kgantshang (BMC Research Notes, 2017)
Abstract Background With the establishment of a new medical college in Botswana to train generalist-doctors and specialists, we set out to explore the career preferences of medical students, factors that influence their choices and attitude to local postgraduate training. Methods A descriptive cross-sectional questionnaire-based study was conducted among medical students in their third to fifth year, at the Faculty of Medicine, University of Botswana. The structured, self-administered questionnaires which were hand-delivered covered demographic characteristics of responders, career choices, preferred location of specialisation and factors that influenced the choices. Results Of the 143 medical students approached, 116 (81.0%) returned completed questionnaires. Of the responders, 102 (87.9%) intend to pursue postgraduate specialisation against 2 (1.7%) who declined; 12 (10.3%) were undecided. The four most preferred specialties which constituted 68.1% were surgery (28.4%), paediatrics (19.0%), internal medicine (12.9%), obstetrics and gynaecology (7.2%). There was male preference for surgery (p = 0.04), while women were drawn more towards paediatrics and psychiatry (p = 0.04 and p = 0.01, respectively). Personal interest and aptitude was considered the most important factor among most responders (46.2%), followed by enjoyment of the posting (19.8%). A high proportion of responders 80 (69.0%) preferred to specialise abroad for better exposure/opportunities (48.3%), while for 15.5%, their preferred courses are not currently available locally. Conclusion Our findings indicated that while four major specialties are preferred, significant gender differences exist with female students leaning towards non-surgical disciplines. Students prefer specialising abroad on the pretext that foreign centres offer better training opportunities, and many specialist programmes are unavailable locally.